LAPTM5–CD40 Crosstalk in Glioblastoma Invasion and Temozolomide Resistance - Berberich, Anne; Bartels, Frederik; Tang, Zili; Knoll, Maximilian; Pusch, Sonja; Hucke, Nanina; Kessler, Tobias; Dong, Zhen; Wiestler, Benedikt; Winkler, Frank; Platten, Michael; Wick, Wolfgang; et al. (Frontiers in Oncology, 2020)
Background Glioma therapy is challenged by diffuse and invasive growth of glioma. Lysosomal protein transmembrane 5 (LAPTM5) was identified as an invasion inhibitor by an in vivo screen for invasion-associated genes. The aim of this study was to decipher the function of LAPTM5 in glioblastoma and its interaction with the CD40 receptor which is intensively evaluated as a target in the therapy of diverse cancers including glioma. Methods Knockdown of LAPTM5 was performed in different glioma cell lines to analyze the impact on clonogenicity, invasiveness, sensitivity to temozolomide chemotherapy and tumorigenicity in-vitro and in-vivo. Expression array was used to elucidate underlying pathways. CD40 knockdown and overexpression were induced to investigate a potential crosstalk of LAPTM5 and CD40. LAPTM5 and CD40 were correlated with clinical outcome of glioma patients. Results Knockdown of LAPTM5 unleashed CD40-mediated NFκB activation resulting in enhanced invasiveness, clonogenicity and temozolomide-resistance that was overcome by NFκB inhibition. LAPTM5 expression correlated with better overall survival in glioblastoma patients dependent on CD40 expression status. Conclusion We conclude that LAPTM5 conveyed tumor suppression and temozolomide sensitation in CD40-positive glioblastoma through the inhibition of CD40-mediated NFκB activation. Hence, LAPTM5 may provide a potential biomarker for sensitivity to temozolomide in CD40-positive glioblastoma.